Bridging Augmented Reality Experience and Purchase Intention: Integrating Attitudinal Ambivalence into an Extended TAM - Cynthia Jessica; Rifelly Dewi Astuti (Journal of Enterprise and Development (JED), 2025)
Purpose: This study explores the impact of augmented reality (AR) technology on purchase intention in Indonesia. By integrating the AR experience framework with an extended Technology Acceptance Model (TAM), the research examines how five dimensions of the AR experience—sensory experience (SE), emotional experience (EE), thinking experience (TE), action experience (AE), and related experience (RE)—affect perceived ease of use (PEOU) and perceived usefulness (PU), which subsequently influence purchase intention (PI), with attitudinal ambivalence (AA) as a mediating factor.Method: A quantitative, cross-sectional survey was conducted with 300 Indonesian respondents, aged 18 to 60, who were recent users of the AR Sephora Virtual Artist. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Result: Findings reveal that the dimensions of the AR experience positively impact PEOU and PU, which subsequently negatively influence AA. PU also directly fosters positive PI, while PEOU does not. Importantly, AA negatively affects PI, underscoring its critical role in consumer decision-making.Practical Implications for Economic Growth and Development: This research offers valuable insights for retailers to optimize AR implementation, thereby enhancing consumer engagement and driving purchase intention. Improving AR usability and effectiveness can reduce consumer uncertainty, strengthen market adoption, and advance digital commerce in the beauty industry.Originality/Value: This study uniquely integrates AA into existing AR adoption models and combines the AR experience framework with an extended TAM, providing novel theoretical contributions to AR in retail and insights into consumer behavior.